--if you lived in the days of the knights - McGovern, Ann.; Andreasen, Dan (New York : Scholastic Inc., 2001)
This book tells what it was like to live in the days of the knights during the Middle Ages.
RL3.
007-010.
Keywords: Knights and knighthood -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Knights and knighthood; Civilization, Medieval